Does the language spoken at home matter for the education, wellbeing, and sense of belonging of the children of immigrants? And does the answer depend on how we analyse it? - Kilpi-Jakonen Elina; Alisaari Jenni (Turun yliopisto, 2022)
Educational disadvantages of children of immigrants have sometimes been linked to speaking a language other than that of school instruction at home. However, thorough investigations of the alleged benefits for immigrant families of adopting the language of the surrounding society are lacking. We used data from a subset of countries in the 2018 Programme of International Student Assessment (PISA) and analysed reading test scores, educational expectations, sense of belonging at school, and subjective wellbeing (positive affect). Our results suggest that the language used at home is not systematically associated with subjective wellbeing or educational expectations. In some countries, switching the home language to that of the destination country is associated with an increased sense of belonging at school and higher reading scores. We discuss these results with reference to ethnic boundary making and how schools and educational systems can respond to the needs of linguistically diverse students.